The Relationship Established Between Indonesian Political and Bureaucratic Official - ., Azhari (International Journal of Engineering and Technology, 2018)
The overlapping responsibility between the political and bureaucratic officials seems not to be avoidable due to the weaknesses of personnel management system. This condition, of course, leads to a clutter in some aspects such as recruitments, promotions, and political structures. This research aims to investigate the relationship between the political and bureaucratic officials in terms of authority which is applied by the officials and the factors that caused the overlapping authority. To do so, a descriptive qualitative analysis was applied in this research since the researcher would like to report the result in what looked like. The saturated data was collected by conducting an in-depth interview and documentations and it was analyzed qualitatively. The findings of the current research showed two models of relationship namely executive assendency and model of Party State Bureaucracy begun from the New-Era to Post New-era. Neither New-Era nor Post New-era are appropriate to be applied in the Southeast Sulawesi. Therefore this research suggested a more appropriate model of bureaucratic management, especially regional governance in Southeast Sulawesi namely the External Model of Executive Assendency or Personal Excecutive Assendency.Â Â